Piezoelectric and ferroelectric measurements on casted target-deposited Al0.45Sc0.45B0.1N thin films - Saha, Kapil; Simeoni, Pietro; Colombo, Luca; Rinaldi, Matteo (Frontiers in Materials, 2025)
This study reports on the characterization of a 45% scandium-doped Aluminum Nitride (AlScN) thin films co-doped with 10% Boron (B). AlScBN thin films were deposited on Si (100) 200 mm wafers using a pulsed DC reactive magnetron sputtering system. A 4″ casted alloy target of Al0.45Sc0.45B0.10 was used in the depositions. The influence of deposition parameters, including target-substrate distance, N2 flow rate, and deposition temperature, on the films’ crystallinity and surface characteristics was investigated on silicon substrates. The crystalline properties of the thin films were characterized using X-ray diffraction (XRD) method with 2θ and ω scans. Based on the characterization performed on Si, process conditions were selected to deliver the best crystallinity while maintaining a stable plasma. Parameters were set to a target-substrate distance of 65 mm, a flow rate of 30 sccm, and a deposition temperature of 300°C. Under these process conditions, a 564 nm-thick sample was fabricated for piezoelectric and ferroelectric characterization. Several capacitive structures of different areas were prepared using a tungsten (W) blanket bottom electrode and platinum (Pt) top electrode on a double-side polished Si substrate. The d33,f coefficient was measured through Piezoelectric Measurement (PZM) technique using Double Beam Laser Interferometry (DBLI) system, yielding a value of ∼25pm/V. Ferroelectric characteristics were assessed through Dynamic Hysteresis Measurement (DHM) and Positive-Up, Negative-Down (PUND) measurement techniques using the same tool. The film exhibited a coercive field Ec+=1.5MV/cm, Ec−=2.5MV/cm and a remnant polarization (2Pr) of 280μCcm−2.